CORRELATION OF PARATHYROID HORMONE-1 RECEPTOR EXPRESSION TO BONE METASTASIS OF BREAST CARCINOMA PATIENTS - Tusta-Adiputra, P. A.; Wibawa-Manuaba,; I. B. T. (BALI MEDICAL JOURNAL, 2014)
Background: Bone metastasis is a common complication of metastasis of breast cancer and it is a unique pathobiology process. The Parathyroid Hormone-related Peptide (PTHrP) is a protein which has an important role in breast cancer cells to invade and infiltrate bones or bone marrow and accelerate angiogenetic process. The objective of this study is to reveal the relationship of PTHrP receptor named Parathyroid Hormone-1 Receptor (PTH1R) expression to bone metastasis in breast cancer patients. Methods: This was an analytical cross-sectional study, applying a non probability consecutive sampling. Samples were divided into two groups, i.e. one group of breast cancer metastasis to bone (+others) and another group with non-bone metastasis. Patients were collected from an existed data base (from medical record, cancer register, histopathology), since 2007. The specimen paraffin blocks were re-examined using IHC technique for PTHrP receptor. The data were analyzed and tested with Chi-Square (X2), otherwise it would be tested using Fisher Exact Test. Each group would be allocated minimal of 17 patients/samples. Results: The Chi-Square test failed to show the association between PTH1R expression in breast cancer patients with bone metastasis (p=0.295). The relative prevalence result for positive PTH1R expression was 1.48. There was no proof that positive PTH1R expression was an associated factor for bone metastasis (95% confidence interval). Conclusion: PTH1R expression is not a factor associated with bone metastasis in breast cancer patients.